Ecological Security Pattern Construction in Typical Oasis Area Based on Ant Colony Optimization: A Case Study in Yili River Valley, China - Hairu Nie; Yang Zhao; Jie Zhu; Ang Ning; Wenhua Zheng (Ecological Indicators)
Establishing Ecological Security Pattern (ESP) is crucial for the harmonious development of society and the environment. Currently, the principal challenges in ecological planning include large contiguous ecological source areas and the accurate determination of ecological corridor widths. This study utilized the InVEST-MSPA-Conefor model, circuit theory, MATLAB, and the ArcGIS platform to analyze the Yili River Valley’s ESP, assess habitat quality, and identify habitat patch types. Results indicate that: (1) Habitat quality is higher in the southern and eastern parts of the river valley. The core area, vital for ecological connectivity, constituted 50.69 % of the study area. (2) Increased ecological resistance was predominantly observed in valley hills and near major transportation routes. (3) Seventy ecological corridors were identified, covering 3671.68 km2 of major and 6968.31 km2 of potential corridors, thus expanding the analysis from “source-line-point” to “source-line-point-plane” and strengthening ecological protection and management strategies. (4) The study proposes an optimization and management strategy of “Three Belts, Two Axes, and One Cluster” grounded in ESP results and local policies. The study advances the understanding of the Yili River Valley’s ecosystem structure, provides strategies for biodiversity conservation and ecological service optimization, and emphasizes the value of integrated, multi-dimensional modeling in ecological planning.